Correlations of morphological parameters for lesions of the wrist joint in patients with posttraumatic nonunion of the navicular bone - Hryhorovskyi, Valeriy; Strafun, Sergey; Timoshenko, Sergey (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2014)
Among the causes of development of posttraumatic wrist joint osteoarthrosis (WJOA) they consider the consequences of scaphoid bone (SB) fractures which are clinically manifesting by pain especially when wrist loading, inflammation of capsule and biomechanic disturbances of wrist joint. Рurpose: to determine pathomorphological changes in tissues of wrist joint underlying of WJOA development, and correlations between some morphological data of wrist joint lesion in patients with consequences of SB fractures. Materials: with using of pathomorphological, biometrical and statistical analysis we investigated 94 resected fragments of the tissues forming a wrist joint, in particular SB (39 objects), semilunar and some other bones (12 objects), joint capsule (43 objects) obtained during fulfillment of corrective interventions according to indications in 55 patients at which WJOA has been connected with consequences of nonunion after SB fracture. Results: it was established that in wrist joint tissues there are various pathological changes with signs of discirculatory, chronic dystrophic-destructive, inflammatory and reparative processes in SB and wrist joint capsule, and the degree of expressiveness and frequency occurrence of distinct gradations of which vary. SB pseudarthrotic surface finds out considerable heterogeneity of pathological changes: along with cases in which deformed surface contains sites formed by reparative chondroid tissue (the most frequent variant), there are cases of pseudarthrotic surface covering with a fibrous tissue or sclerosed spongy bone denudation (the most rare variant). The SB articular surfaces removed in patients with SB pseudarthrosis approximately with identical frequency find out degree of prevailing dystrophic-destructive changes which correspond to distinct stages WJOA. In spongiosa of the SB one meets osteonecroses of different size: small and large interstitial, and also large focal frequencies of occurrence of which are comparable in biopsy-histological material. Morphological parameters of wrist joint tissues condition find out correlations of different force and significance degree among themselves. There are pairs of indices that are the most closely connected: "hypertrophy and hyperplasia of the joint capsule synovial layer villi" and "activity of synovitis" as well as "dystrophic-destructive changes of SB articular surface" and "hypertrophy and hyperplasia of the joint capsule synovial layer villi". Conclusion. Morphological parameters which reflect the tissues conditions of SB, other bones of the wrist, joint capsule in patients with consequences of SB fractures, are notable by considerable variability and stay among themselves in correlations of different closeness, sign and significance (within the scope of research performed).